Klassisch, agil oder hybrid? Der Anforderungs-Check für das Projektmanagement in KMU - Philip Legerski; Susanne Theresia Weber (IU Internationale Hochschule, 2022)
– The collection of requirements in the project is common practice. However, the requirements check serves the structured analysis and presentation of the requirements for project management in SMEs. Whether classical, agile or hybrid project management is applied is thus no longer a subjective assessment of individuals. The aim is to select the right method and provide targeted support to the project team in order to professionalize project management. Project management in small and medium-sized SMEs must not be bulky, but must adapt standards, best practices and methods to the company and must remain practicable but secure. Likewise, the usually very scarce resources must be taken into account. Whether classic, agile or hybrid project management: The authors believe that the choice can be narrowed down on the basis of clear criteria. It is not a question of taste or trend, but of requirements! Project management is not an end in itself. Determining the requirements internal and external to the organization is the first step before project management is structured. A project has certain characteristics that must be taken into account and phases in which certain activities must take place. Projects can also be categorized to determine the right approach, the stakeholders involved and therefore the right requirements. Any SME can very efficiently approach the right choice of approach in a structured way using the described procedure, select the appropriate methods at the critical points in project management and thus support the project team in a targeted manner.
Keywords: 650; Projektmanagement; klassisch; agil; hybrid; Transformation; Unternehmensentwicklung; Unternehmensorganisation; Management